Identification of Prognostic Signature and Gliclazide as Candidate Drugs in Lung Adenocarcinoma - Cheng, Yang; Hou, Kezuo; Wang, Yizhe; Chen, Yang; Zheng, Xueying; Qi, Jianfei; Yang, Bowen; Tang, Shiying; Han, Xu; Shi, Dongyao; Wang, Ximing; Liu, Yunpeng; et al. (Frontiers in Oncology, 2021)
Abstract Background: Lung adenocarcinoma (LUAD) is the most common pathological type of lung cancer, with high incidence and mortality. To improve the curative effect and prolong the survival of patients, it is necessary to find new biomarkers to accurately predict the prognosis of patients and explore new strategy to treat high-risk LUAD. Methods: A comprehensive genome-wide profiling analysis was conducted using a retrospective pool of LUAD patient data from the previous datasets of Gene Expression Omnibus (GEO) including GSE18842, GSE19188, GSE40791 and GSE50081 and The Cancer Genome Atlas (TCGA). Differential gene analysis and Cox proportional hazard model were used to identify differentially expressed genes with survival significance as candidate prognostic genes. The Kaplan-Meier with log-rank test was used to assess survival difference. A risk score model was developed and validated using TCGA-LUAD and GSE50081. Additionally, The Connectivity Map (CMAP) was used to predict drugs for the treatment of LUAD. The anti-cancer effect and mechanism of its candidate drugs were studied in LUAD cell lines. Results: We identified a 5-gene signature (KIF20A, KIF4, KRT6A, LIFR, and RGS13). Risk Score (RS) based on 5-gene signature was significantly associated with overall survival (OS). Nomogram combining RS and clinical pathology parameters could potently predict the prognosis of patients with LUAD. Moreover, gliclazide was identified as a candidate drug for the treatment of high-RS LUAD. Finally, gliclazide was shown to induce cell cycle arrest and apoptosis in LUAD cells possibly by targeting CCNB1, CCNB2, CDK1 and AURKA. Conclusion: This study identified a 5-gene signature that can predict the prognosis of patients with LUAD, and Gliclazide as a potential therapeutic drug for lung adenocarcinoma. It provides a new direction for the prognosis and treatment of patients with lung adenocarcinoma.